Evaluation of Some Immunological Parameters in Patients with COVID-19 in Mosul City, Iraq - Mohammed Fadhil Haddad; Fawwaz Fadhil Ali; Mohammed H. Sharif Alkatib; Shihab A. Al-Bajari (Medical Journal of Babylon)
Background: Coronavirus disease 2019 (COVID-19), also known as severe acute respiratory syndrome coronavirus 2, is a viral disease caused by a coronavirus involved in severe acute respiratory syndrome that causes mild, moderate, and severe respiratory system infections. World Health Organization has documented that COVID-19 infections are rapidly spreading and have become a global pandemic. Objectives: This study aimed to investigate the association of specific immunological parameters in COVID-19-infected patients in Mosul, Iraq. Materials and Methods: A total of 268 confirmed COVID-19 patients were enrolled in this study (129 males and 139 females). One hundred seventy-nine healthy participants were chosen randomly (81 males and 98 females) as a control. All patients admitted to Al-Salam Teaching Hospital, Iraq from February to May 2021 were included in the study. Blood samples were collected from the participants for serum to estimate levels of C-reactive protein (CRP), interleukin-6 (IL-6), and interleukin-10 (IL-10) using an enzyme-linked immunosorbent assay technique. The total white blood cells (WBC), neutrophils, lymphocytes, and monocytes were also measured. Results: This study revealed that most COVID-19 patients showed high levels of serum CRP, IL-6, and IL-10. The patients with COVID-19 had a significantly higher total WBC count than healthy controls, with 12.21 and 6.93 cells per 103/L, respectively. However, the results showed a reduction in lymphocyte counts in COVID-19 patients. The hematological analysis was statistically significant for all parameters that were estimated in all COVID-19 patients, and controls and was compatible with clinical significance (P = 0.005). Conclusion: Infections with COVID-19 may elevate the levels of serum CRP, IL-6, and IL-10. Therefore, monitoring these immunological markers is essential, particularly in individuals with severe COVID-19 infection.